Escenarios multiculturales en la escuela y su influencia en actitudes y bienestar social del profesorado de primaria - Alonso, Lorena (2014)
The present study analyzes the impact of different multicultural school contexts in a sample of primary teachers. In this way we took on consideration different models of multicultural education and the analysis of relevant psycho-social variables such as: intercultural sensibility, attitudes towards multiculturalism at schools, types of message styles in situations of conflict, social well being and teacher’s stress. There for, three types of contexts were taken into account: Control Group: schools without foreign scholars or >1%, Group 1: schools upon 10% of foreign students, and Group 2: schools with 30% or more foreign scholars. Our findings show significant differences between the three types of multicultural settings on the teacher’s attitudes and perceptions. Being the teachers from Group 2 evidence more intercultural sensitivity, more social well being and more positive attitudes against multiculturalism at schools.